Enhancing Students' Knowledge-Based Economy Skills at Sultan Qaboos University - Nour Eldin Elshaiekh; Ahmed Shehata; Noura Al Hosni (MDPI AG, 2024)
This study examines the readiness of Sultan Qaboos University (SQU) students for the knowledge-based economy, focusing on their awareness, perceptions, and skills. As Oman transitions towards a knowledge-based economic model, understanding and enhancing students' preparedness has become crucial. This research employs a quantitative approach, utilizing a questionnaire distributed to SQU students across various colleges and academic levels, achieving a 66.04% response rate. The key findings reveal that while many students consider knowledge economy skills very important, some express neutral awareness about these skills. Students ranked creativity and innovation (85.82%) and critical thinking and problem solving (85.11%) as the most essential skills. The study identifies significant relationships between enhancing students' knowledge-based economy skills (ESKBE) and both awareness of the knowledge-based economy (AWS) and the impact of technology on education and employment (ITEE). Students generally view the knowledge economy positively, with 55% agreeing it will have a positive societal impact. However, they recognize challenges, including resistance to change (53.5% agreement) and limited access to education and training (49.3% agreement). The need for government involvement in addressing these challenges was strongly emphasized (54.3% agreement). Based on these findings, the study recommends that SQU enhance its curriculum to explicitly develop key skills, improve awareness of knowledge economy demands, further integrate technology into educational practices, strengthen industry partnerships, promote lifelong learning initiatives, and engage more actively with policymakers. This paper also provides a unique look at higher education's role in the changing economy, as seen through graduates. It offers empirical evidence for the necessity of universities to change to serve the knowledge economy and, at the same time, make a case on how complex this transformation is. The results matter not only for SQU but also-in a more general sense, at least as far as knowledge-based economies are concerned-globally with respect to higher education institutions.